Epidemic dropsy: A mimic of scleroderma? - Anupam Wakhlu; Rasmi Ranjan Sahoo (Indian Journal of Rheumatology)
Systemic sclerosis (SSc) is an autoimmune connective tissue disease involving the skin and internal organs and characterized pathologically by microvascular damage and increased deposition of connective tissue. Skin changes seen in SSc include edema, inflammation, induration, thickening, and progressive skin fibrosis. Histologically, skin fibrosis, accumulation of compact collagen in the dermis, effacement of rete pegs, infiltration by CD4+ T cells, and skin atrophy are observed. The “toxic oil syndrome” reported from Spain caused an outbreak of a scleroderma-like illness and was caused by ingestion of contaminated rapeseed cooking oil. Epidemic dropsy is caused by ingestion of mustard oil contaminated with the oil of Argemone mexicana. The major alkaloids in Argemone oil are sanguinarine and dihydrosanguinarine. These alkaloids produce widespread capillary dilatation, increased capillary permeability, and endothelial proliferation, akin to the toxic oil syndrome. Cutaneous manifestations include erythematous and tender bilaterally symmetrical pitting edema usually involving lower limbs, skin thickening and tethering, pigmentation, and presence of telangiectasias. The dermatopathology observed in epidemic dropsy includes atrophy and flattening of rete pegs, hypertrophy of and deposition of collagen, vascular dilatation and proliferation, and subcutaneous inflammation and fibrosis. Epidemic dropsy usually presents with subacute multisystem involvement, which may mimic a connective tissue disease. Skin involvement in epidemic dropsy may closely mimic cutaneous manifestations in SSc, both clinically and histologically. Thus, the clinician needs to be aware that epidemic dropsy with cutaneous involvement, especially if encountered sporadically, may be mistakenly diagnosed as scleroderma.